PROSPEK PENGEMBANGAN TANAMAN SUKUN DITINJAU DARI KANDUNGAN KIMIA DAN ASPEK LAINNYA - Gusmailina Gusmailina; Sri Komarayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Breadfruit (Artocarpus artilis Forsberg) is a multipurpose tree species which is suitable to be extensified. The report deals with. chemical analysis of breadfruit wood. The results indicated that cellulose contenl 53.58 %; lignin cotuet 28.09%; pentosan content 14.00%; solubitity in cold water 3.13 % ; in hot waler 4. 14 %; alcohol-benzena 3. 40% and in NaOH 1 % 20. 03 % , moisture content 10.14 %; ash comesu 3. 60%; silica content 3. 10% and calorific value 4368.82 kcal/gr. Baseak on the components, breadfruit wood can be utilized as sources of raw material for pulp and paper or rayon. Besides it is also an alternative for food source and source of income for rural people.